PENGARUH STRATEGIC LEADERSHIP, INNOVATION DAN CORPORATE CULTURE TERHADAP COMPETITIVE ANDVANTAGE SERTA IMPLIKASINYA TERHADAP CORPORATE PERFORMANCE (STUDI KASUS PADA Bank BJB syariah) - Renaldi Wahyudin, Yusri; Zulkifli; Derriawan (SEKOLAH PASCASARJANA PRESS, 2022)
Conventional and Islamic banks are said to be good if they are able to develop and improve their performance both financially and operationally. In Islamic bank bjb based on empirical data for 2017-2019, the financial performance of Islamic bank bjb is not good, it can be seen from the operating profit and the NPF (non-performing financial) ratio that does not meet the target. Therefore, Islamic bank bjb needs to improve financial performance through a competitive advantage strategy. So that the purpose of this study is to determine the effect of strategic leadership, innovation and corporate culture on competitive advantage and its implications for corporate performance. The method used is descriptive analysis verification, path analysis techniques using Structural Equation Modeling (SEM) with the SmartPLS program. Hypothesis test results show that corporate culture has no significant effect on competitive advantage; strategic leadership has no significant effect on competitive advantage; corporate culture has a significant effect on corporate performance; innovation has a significant effect on competitive advantage; innovation has a significant effect on corporate performance; Competitive advantage has a significant effect on corporate performance. Furthermore, the leadership strategy variables, innovation and corporate culture contributed to competitive advantage by 45.6% and to corporate performance by 68%. This research is expected to provide input to Islamic bank bjb that in order to improve business performance the company needs to determine the competitive advantage of Islamic bank bjb, by developing leadership skills in strategic leadership, developing innovative strategies for products and services that have competitiveness and promotional strategies including the mix. and marketing concepts as well as technological developments and competitiveness strategies of competitors